Urbanoid Northwest: an identity for a railway complex - Bispo de Souza, Jadher Marcos (Universidad de Lima. Carrera de Arquitectura, 2020)
Campo Grande’s urbanization was linked to a railway track, giving rise to new neighborhoods and cultures that were mixed with the already existing population. In the mid-90s, the railway track deactivation and removal from its urban network occurred, and, in this setting, railway spaces and their history started losing their identity. As a Brazilian state’s capital, alternatives with utopian solutions could be provided to the complex, resulting in 21st-century projects that could be used for public transportation, and thus generate a change of direction in the economy and tourism. This paper discusses the reality found in Southern Mato Grosso, as well as itshistorical and urban space evolution.